Coexistence of GLIM-defined malnutrition and sarcopenia have negative effect on the clinical outcomes in the elderly gastric cancer patients after radical gastrectomy - Chen, Wei-Zhe; Zhang, Xian-Zhong; Zhang, Feng-Min; Yu, Ding-Ye; Chen, Wen-Hao; Lin, Feng; Dong, Qian-Tong; Zhuang, Cheng-Le; Yu, Zhen (Frontiers in Nutrition, 2022)
Background: Malnutrition and sarcopenia are common in elderly gastric cancer patients, which are also interrelated and affect each other. We aimed to determine the characteristics of coexistence of malnutrition and sarcopenia in the elderly gastric cancer patients and investigate the predictive roles of malnutrition and sarcopenia on clinical outcomes. Methods: Between 2014 and 2019, a total of 742 elderly gastric cancer patients were enrolled. Malnutrition and sarcopenia were diagnosed according to the most recent diagnostic criteria. Patients were divided into four groups according to presence of these two symptoms. Clinical characteristics, short- and long-term outcomes were compared among four groups. The independent risk factors of complications and survival were evaluated using univariate and multivariate analyses. Results: Of all patients, 34.8% were diagnosed with malnutrition and 34.0% were diagnosed with sarcopenia. Patients with both malnutrition and sarcopenia had the highest rate of total (P < 0.001), surgical (P = 0.003), and medical complications (P = 0.025), and the highest postoperative hospital stays (P < 0.001) and hospitalization costs (P < 0.001). They also had the worst overall survival (P < 0.0001) and disease-free survival (P < 0.0001). Sarcopenia and Charlson Comorbidity Index (≥2) were independent risk factors for total complications. Hypoalbuminemia and malnutrition were non-tumor-related independent risk factors for overall survival and disease-free survival. Conclusions: Malnutrition and sarcopenia had superimposed negative effects on elderly gastric cancer patients. Preoperative geriatric evaluation including screening for malnutrition and sarcopenia are recommended for all elderly gastric cancer patients for accurate treatment strategy.